Co‐expression of GR79 EPSPS and GAT yields herbicide‐resistant cotton with low glyphosate residues. Issue 12 (26th May 2017) - Liang, Chengzhen; Sun, Bao; Meng, Zhigang; Meng, Zhaohong; Wang, Yuan; Sun, Guoqing; Zhu, Tao; Lu, Wei; Zhang, Wei; Malik, Waqas; Lin, Min; Zhang, Rui; et al.
Summary: Glyphosate‐resistant (GR) crops have been adopted on a massive scale by North and South American farmers. Currently, about 80% of the 120 million hectares of the global genetically modified (GM) crops are GR crop varieties. However, the adoption of GR plants in China has not occurred at the same pace, owing to several factors including, among other things, labour markets and the residual effects of glyphosate in transgenic plants. Here, we report the co‐expression of codon‐optimized forms of GR79 EPSPS and N‐acetyltransferase ( GAT ) genes in cotton. We found five times more resistance to glyphosate with 10‐fold reduction in glyphosate residues in two pGR79 EPSPS ‐ pGAT co‐expression cotton lines, GGCO2 and GGCO5. The GGCO2 line was used in a hybridization programme to develop new GR cottons. Field trials at five locations during three growing seasons showed that pGR79 ‐ pGAT transgenic cotton lines have the same agronomic performance as conventional varieties, but were USD 390‐495 cheaper to produce per hectare because of the high cost of conventional weed management practices. Our strategy to pyramid these genes clearly worked and thus offers attractive promise for the engineering and breeding of highly resistant low‐glyphosate‐residue cotton varieties.